Shift in Naming Bugis to Early Childhood in Kindergarten Marioriwawo District Soppeng Regency - Nurul Hiqmahtillah Jusman; Kembong Daeng (Panrita: Jurnal Bahasa dan Sastra Daerah serta Pembelajarannya, 2021)
This study aims toThis type of research is qualitative research. The techniques used to obtain data in this study were interview techniques and documentation techniques. The techniques used to analyze the data, namely: data collection, data reduction, data presentation and drawing conclusions. The results of this study found a shift in naming, namely: (1) Giving names to the age group 50 years and over prioritizes the reasons given the name. The names are identical with names starting with i and some ending in g. Consists of two points, namely the first, based on the meaning which is divided into prayer (hope), the time of birth and cause and effect. The second, based on aids or rules. (2) Giving names to the age group of children is far from the element of bugs. The naming of children is also divided into two points, namely the first, based on the meaning contained in the prayer of hope, the time of birth and the order in the family. The second is based on rules and forms. (3) The shift that occurs in naming from the age of 50 years and over to children has a very large shift. In this village at this time there is no longer any element of nudity.